The trans‐Atlantic slave trade and local political fragmentation in Africa1. (1st June 2016) - Obikili, Nonso
Abstract : This article examines the possibility that the trans‐Atlantic slave trade influenced the political institutions of villages and towns in precolonial Africa. Using anthropological data, it shows that villages and towns of ethnic groups with higher slave exports were more politically fragmented during the precolonial era. Instrumental variables are used to show that the relationship is causal. It is argued that this fragmentation is important for relative economic development because it still influences political institutions today. This argument is supported by the use of more contemporary data to show that in contemporary Nigeria and Tanzania, areas with higher levels of precolonial political fragmentation have a higher incidence of bribery.